Improving Pain Care Using Psychosocial Screening and Patient Education among Veterans. (2nd October 2022) - Cosio, David
Abstract: Pain education programming is considered one avenue of treatment for comorbid chronic pain and mental health disorders. The purpose of the current single group, longitudinal ex post facto study was to determine whether participation in a pain education program would decrease symptoms on psychiatric and functional disability domains using emerging screening measures. A sample of 90 Veterans participated in a pain education program at a Midwestern VA Medical Center between November 1, 2013 and October 31, 2014. The Pain Education School program is a comprehensive program that is open to all Veterans and introduces them to different modalities that deal with chronic pain available in the VA hospital. All participants completed pre- and post-education screening measures. Paired-samples t -tests were conducted to evaluate the impact of the pain education program on Veterans' scores on these measures. The current study found a significant difference in depression ( p =.005; d =.18), mobility ( p =.000; d =.47), social participation ( p =.001; d =.30), and total functional disability scores ( p =.001; d =.30) upon completion of the program. The current study serves as a model of how to use emerging screening measures and education programming to enhance clinical practice and decision-making to better address Veterans' needs.